Strengthening Students Entrepreneurial Mindset through Participatory Learning Implications for Entrepreneurial Motivation and Business Sustainability - Adiba Maulidiyah; Moch. Salman Alfarizi; Nensa Widiawati Sukma; Muhammad Alfi Syahrin (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This community engagement program aimed to strengthen students’ entrepreneurial mindset through participatory learning and to examine its implications for enhancing entrepreneurial motivation and business sustainability among students of Ahmad Dahlan Institute of Probolinggo. The program employed the Participatory Learning and Action (PLA) approach, implemented through several stages, including needs assessment, material delivery, interactive discussions, case studies, business development planning, mentoring, and activity evaluation. Data were collected through observation, documentation, questionnaires, and participatory evaluation and were analyzed using a descriptive qualitative approach. The findings revealed that participatory learning effectively improved students’ understanding of the entrepreneurial mindset concept, strengthened their ability to identify business opportunities, increased their self-confidence in initiating and developing business ventures, and fostered higher levels of entrepreneurial motivation. Furthermore, participants demonstrated an enhanced understanding of the importance of innovation, digital technology adaptation, and business planning as critical factors in ensuring business sustainability. These findings indicate that participatory learning represents an effective approach to developing students’ entrepreneurial competencies by holistically integrating entrepreneurial knowledge, skills, and attitudes